The Effect of Offline and Online Learning System on Elementary School Students' Stress Levels During a Pandemic - Siti Masyithoh; Sindi Lestari (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThe entry of the Covid-19 virus into Indonesia has a direct impact, especially in the education sector. The most felt impact is the implementation of the learning process from home with or without using the internet network. Learning using the internet is known as online learning while learning without using the internet is known as offline learning. This study aims to determine the difference in stress levels of students who use offline learning systems and students who use online learning systems during a pandemic. This study uses a quantitative method with an experimental design of posttest only control group design.. This research was conducted at SDIT Nurul Amal with a total sample of 52 students with details of 36 students using the offline learning system and 16 students using the online learning system. Data collection was carried out using an instrument in the form of a student stress questionnaire with a Likert scale model containing 59 items with a valid value (α = 0.279). Data analysis used Independent Sample t-Test. The results of this study indicate that there are differences in the stress level of students who use offline learning systems and students who use online learning systems as indicated by the value of t count = 10.03 with p = 0.039 (p <0.05) and the value of Sig. 2 (tailed) 0.00 (Sig. 2 tailed < 0.05). This shows that there are differences in the stress levels of students who use offline learning systems and students who use online learning systems. AbstrakMasuknya virus Covid-19 ke Indonesia berdampak langsung terutama pada sektor pendidikan. Dampak yang paling dirasakan adalah pelaksanaan proses belajar dari rumah dengan atau tanpa menggunakan jaringan internet. Pembelajaran dengan menggunakan internet disebut pembelajaran online sedangkan pembelajaran tanpa menggunakan internet disebut pembelajaran offline. Penelitian ini bertujuan untuk mengetahui perbedaan tingkat stres siswa yang menggunakan sistem pembelajaran offline dan siswa yang menggunakan sistem pembelajaran online pada masa pandemi. Penelitian ini menggunakan metode kuantitatif dengan desain eksperimen posttest only control group design. Penelitian ini dilakukan di SDIT Nurul Amal dengan jumlah sampel 52 siswa dengan rincian 36 siswa menggunakan sistem pembelajaran offline dan 16 siswa menggunakan pembelajaran online. Sistempengumpulan data dilakukan dengan menggunakan instrumen berupa angket stres siswa dengan model skala Likert yang berisi 59 item dengan nilai valid (α = 0,279). Analisis data menggunakan Independent Sample t-Test. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan tingkat stres siswa yang menggunakan sistem pembelajaran offline dan siswa yang menggunakan sistem pembelajaran online yang ditunjukkan dengan nilai t hitung = 10,03 dengan p = 0,039 (p < 0,05) dan nilai dari Sig. 2 (berekor) 0,00 (Sig. 2 berekor < 0,05). Hal ini menunjukkan bahwa terdapat perbedaan tingkat stres siswa yang menggunakan sistem pembelajaran offline dan siswa yang menggunakan sistem pembelajaran online. How to Cite: Masyithoh. S.,  Sindi. L. (2022). The Effect of Offline and Online Learning System on Elementary School Students' Stress Levels During a Pandemic. TARBIYA: Journal of Education in Muslim Society, 9(2), 63-76. doi:10.15408/tjems.v9i1. 24690.